2021
DOI: 10.1016/j.celrep.2020.108610
|View full text |Cite
|
Sign up to set email alerts
|

MCT1 Deletion in Oligodendrocyte Lineage Cells Causes Late-Onset Hypomyelination and Axonal Degeneration

Abstract: SUMMARY Oligodendrocytes (OLs) are important for myelination and shuttling energy metabolites lactate and pyruvate toward axons through their expression of monocarboxylate transporter 1 (MCT1). Recent studies suggest that loss of OL MCT1 causes axonal degeneration. However, it is unknown how widespread and chronic loss of MCT1 in OLs specifically affects neuronal energy homeostasis with aging. To answer this, MCT1 conditional null mice were generated that allow for OL-specific MCT1 ablation. We obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 38 publications
(49 reference statements)
4
58
0
Order By: Relevance
“…Global heterozygosity of the Slc16a1 gene (which encodes the MCT-1 transporter) in mice causes axonal pathology by eight months of age, including axonal swellings, degeneration, and enlarged axonal mitochondria (Lee et al, 2012). In contrast, a more recent study found that conditionally ablating Slc16a1 within mature oligodendrocytes (using MOG-Cre) resulted in a more modest and delayed axonopathy, becoming apparent from postnatal day 750 (Philips et al, 2021). This suggests that some of the neurodegeneration in the global heterozygous mice is likely secondary to expression of monocarboxylate transporters in cell types other than myelinating oligodendrocytes, such as astrocytes.…”
Section: Oligodendrocytic Shuttling Of Monocarboxylates and Glucose Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Global heterozygosity of the Slc16a1 gene (which encodes the MCT-1 transporter) in mice causes axonal pathology by eight months of age, including axonal swellings, degeneration, and enlarged axonal mitochondria (Lee et al, 2012). In contrast, a more recent study found that conditionally ablating Slc16a1 within mature oligodendrocytes (using MOG-Cre) resulted in a more modest and delayed axonopathy, becoming apparent from postnatal day 750 (Philips et al, 2021). This suggests that some of the neurodegeneration in the global heterozygous mice is likely secondary to expression of monocarboxylate transporters in cell types other than myelinating oligodendrocytes, such as astrocytes.…”
Section: Oligodendrocytic Shuttling Of Monocarboxylates and Glucose Tmentioning
confidence: 99%
“…This suggests that some of the neurodegeneration in the global heterozygous mice is likely secondary to expression of monocarboxylate transporters in cell types other than myelinating oligodendrocytes, such as astrocytes. Nevertheless, the late-onset axonal pathology seen in oligodendrocyte conditional knockouts of Slc16a1 clearly indicates that oligodendrocyte provision of metabolites is required for axonal integrity, at least in the aging CNS (Philips et al, 2021). Given (Lee et al, 2012) found reduced expression of MCT1 in the cortex of ALS patients and oligodendrocytes of SOD1 mutants it is tempting to speculate that enhancing oligodendrocyte provision of glycolysis products to axons could be neuroprotective in disease contexts.…”
Section: Oligodendrocytic Shuttling Of Monocarboxylates and Glucose Tmentioning
confidence: 99%
“…This metabolic coupling is highly regulated by axonal activity and is essential for its function, for reviews see Saab et al (2013); Philips and Rothstein (2017). The importance of this "symbiotic" relationship is highlighted by work showing that oligodendrocyte-specific deletion of MCT1 causes axonal degeneration in aged mice (Lee et al, 2012;Philips et al, 2021). Perturbation in components of compacted myelin, such as myelin basic protein, which are responsible increasing conduction velocity do not cause axonal degeneration, indicating that compacted and uncompacted myelin have different roles.…”
Section: Myelin Modulates Network Properties In Response To Environmental Cuesmentioning
confidence: 99%
“…Moreover, decreased expression of this transporter in oligodendrocytes has been reported in human brains during neurodegenerative diseases such as Creutzefeld Jacob [85], Alzheimer's disease [86,87], and Amyotrophic Lateral Sclerosis (ALS) [87]. A recent paper examined the effects of conditional MCT1 deletion in oligodendroglial lineage and myelinating oligodendrocytes [88]. The results show that loss of MCT1 did not affect developmental myelination or early axonal energy homeostasis.…”
Section: Monocarboxylates (Ketone Bodies and Lactate) And Their Transporters In Oligodendrogliamentioning
confidence: 99%